Modeling and Real-time Visual Simulation of Multi-axis CNC Machine Tools for Digital Twins - MENG Boyang; SUN Wenxing; YUE Caixu; ZHU Tongjie; FU Zizhen; LIU XianLi (Journal of Harbin University of Science and Technology, 2025)
As the core engine of intelligent manufacturing, digital twins hold immense potential in the fields of virtual simulation and machining visualization. However, traditional offline digital twin modeling methods rely on the accuracy of preset parameters for fidelity, resulting in poor synchronization between simulation results and physical entities. This paper proposes a digital twin modeling method for multi-axis machine tools oriented towards real-time simulation. Through theoretical hierarchical architecture design and kinematic derivation of machining interaction behaviors, a real-time data-driven digital twin model of the machine tool is constructed. By combining the machine tool OPC UA data communication method with the cutting process simulation method driven by the UE5 engine, a real-time visualization mapping model of machining surface roughness-material color is constructed, achieving high-fidelity simulation of the actual machining process and real-time visualization of machining. Finally, a digital twin platform for machine tools is built using the VMC-C50 cradle-type five-axis machining center as a case study, verifying the maturity of the digital twin model and the reliability of the real-time simulation process.